Effectiveness of active dynamic and passive thermography in the detection of maxillary sinusitis. Issue 4 (8th August 2021) - Singh, Jaspreet; Arora, Ajat Shatru
ABSTRACT: This paper presents a novel approach for sinusitis detection by means of thermography. So far, the role of passive static thermography (PST) for diagnosing the sinusitis has been remarked by many studies. But, it has not been proved as an effective approach for sinusitis detection. With this aim, the automatic and active dynamic thermography (ADT) based approach has been proposed. The study has four steps: (a) data acquisition, PST and ADT of 19 control subjects and 16 sinusitis patients; (b) automatic extraction of maxillary regions; (c) thermal data processing; and (d) thermal data analysis. The effectiveness of ADT and PST approach has been evaluated by comparing their outcomes with physical examinations. Consequently, PST shows failure in the detection of maxillary sinusitis, whereas the outcomes of ADT highly correlate with physical examinations. The frequency analysis of ADT data shows 90% accuracy for sinusitis detection with sensitivity and specificity of 77.27% and 95.83%, respectively. In ADT, it has been observed that the thermal profiles of sinusitis patients are significantly different from those of control group during self-warming phase. Hence, the study shows the encouraging results towards the application of ADT in the diagnosis of sinusitis.